The food consumption and eating behaviour of Malaysian urbanites: Issues and concerns - Noraziah Ali; Mohd Azlan Abdullah (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
Food and the culture of eating of the Malaysian urban society has undergone some form of transformation. This paper takes a closer look at the pattern of the Malaysian urbanites’ food consumption and eating behaviour, which w a s no longer anchored in the household. Instead, eating-out was practiced at the many food premises (including those operating 24 hours a day), available in the urban setting. Based on secondary data from several case studies in Bandar Baru Bangi (Selangor), Jitra (Kedah) and Segamat (Johor) it was found that the practice of eating-out had become a trend among urban workers, students and even families because they could not go home to eat or b e c aus e there wa s no food at home. Factors such as working away from home, working mothers, and food varieties (both local and international) served at many premises encouraged the practice of eating-out. Restaurants, food courts and food stalls w e r e servicing not only those who wanted to eat at meal times, but also those who wanted to enjoy food with friends/family members in a festive and relax manner. Food caterers were also available to serve at formal functions (meetings, seminars) in offices and at home during religious and family occasions. However, l a c k o f c onsideration of nutrient contents, irregular eating time, poor food quality and premises’ cleanliness might expose the practitioner to health, social, familial and even safety risks .